A novel approach to single‐cell analysis reveals intrinsic differences in immune marker expression in unstimulated BALB/c and C57BL/6 macrophages. Issue 20 (2nd September 2022) - Breda, Jeremie; Banerjee, Arka; Jayachandran, Rajesh; Pieters, Jean; Zavolan, Mihaela
Abstract : The origin of functional heterogeneity among macrophages, key innate immune system components, is still debated. While mouse strains differ in their immune responses, the range of gene expression variation among their pre‐stimulation macrophages is unknown. With a novel approach to scRNA‐seq analysis, we reveal the gene expression variation in unstimulated macrophage populations from BALB/c and C57BL/6 mice. We show that intrinsic strain‐to‐strain differences are detectable before stimulation and we place the unstimulated single cells within the gene expression landscape of stimulated macrophages. C57BL/6 mice show stronger evidence of macrophage polarization than BALB/c mice, which may contribute to their relative resistance to pathogens. Our computational methods can be generally adopted to uncover biological variation between cell populations. Abstract : By analysing the gene expression profiles of individual peritoneal macrophages from BALB/c and C57BL/6 mice in the absence of any specific antigen stimulation, we found intrinsic cell‐to‐cell variability along the previously reported axes of M1/M2 polarization. The gene expression bias was stronger in C57BL/6 compared to BALB/c macrophages.